Определение электромагнитных параметров и фазовых соотношений в турбогенераторах автоматизированным расчетом магнитного поля в программной среде FEMM - Милых, В.И.; Полякова, Н.В. (Електротехніка і електромеханіка, 2016)
Представлены теоретические основы расчета электромагнитных величин и их фазовых соотношений для турбогенераторов. Это реализуется путем численных расчетов магнитного поля в программном пакете FEMM. Расчеты
автоматизированы посредством созданной программы на алгоритмическом языке Lua. Она управляет расчетами и
организует выдачу результатов в текстовый файл. Представленный скрипт Lua универсален и может послужить
прототипом аналогичного программного обеспечения для других типов электрических машин Надані теоретичні основи розрахунку електромагнітних величин і їх фазових співвідношень для турбогенераторів. Це
реалізується шляхом числових розрахунків магнітного поля у програмному середовищі пакету FEMM. Розрахунки автоматизовані за допомогою створеної програми на алгоритмічній мові Lua. Вона управляє розрахунками і організовує
видачу результатів в текстовий файл. Представлений скрипт Lua є доволі універсальним і може послужити основою
щодо створення аналогічного програмного забезпечення для інших типів електричних машин The theoretical bases of calculation of electromagnetic quantities and time-phase relationship are presented for the turbogenerators. This is done by numerical calculations of the magnetic field in the software environment package FEMM (Finite
Element Method Magnetics). A program which controls calculations and organizes the issuance of the results to a text file is
created on the algorithmic language Lua. The program is universal in terms of a turbo-generator models, as well as steadystate modes of their work with a minimum of input data. The
exciting current of the rotor and the phase currents of threephase stator winding in accordance with their initial phase are
given for the calculation of the magnetic field. The key function
for the analysis of electromagnetic parameters is the calculated
angular function of the magnetic flux phase stator winding. The
expansion in the harmonic series is carried out and amplitude
and initial phase are received for this function. Next, the phase
EMF and voltage, phase shifts between all values, active power,
electromagnetic torque, the magnetic flux in the gap and other
parameters are determined. The presented Lua script is a prototype for a similar calculation software of electric machines of
other types